Clinical and radiological bone density study of immediate placement of coral coated dental implant - Tahe, Ali Abdul Kawi Ali (2006)
The placement of implants immediately or shortly after tooth extraction has proven to be a predictable treatment strategy with a very high rate of success. Immediate implant placement has several advantages, such as reduction of the number of surgical treatments, reduction of the time between tooth extraction and placement of the definitive prosthetic restoration, prevention of bone resorption, and preservation of the alveolar ridge in terms of height and width, which in turn has esthetic and functional benefits. The use of coated implants with a biocompatible material may bring better integration of the implant. The aim of this study was to determine clinically the efficacy of bone healing of immediate dental implantation with coral augmentation at the bone - implant interphase and to compare radiographic bone density around immediate dental implants with and without coral augmentation. Thirteen patients were selected for this study. The inclusion criteria were healthy patients, aged between 18 and 40 years old, indicated for single tooth extraction, without endo-perio lesion at site of extraction and extraction socket was left with intact four walls while exclusion criteria were patients with systemic disease, and extraction socket has lost one or more wall. Eight patients in the test group had immediate implant with coral coating and five patients in the control group used non- coated implant. Two patients were dropped from the study in the test group. Clinical and densitometric assessments were done at one, two and three weeks and four months postoperative. Clinically all the eleven patients in both groups showed normal wound healing. Densitometric analysis showed that the bone density was significantly higher in the immediate coral coated implant group compared to the control group on at least one point around the implant (p<001 ). The values for densitometric analysis at five different points were higher in coral coated implant group. densitometric analysis at five different points were higher in coral coated implant group. However, the difference was significant only at the coronal mesial and midway distal points, (p<0.002 and p<0.024) respectively. Based upon the results of the present study, it can be concluded that locally produced coral seemed to be a suitable material for coating the surface of implants since it provided primary stability to the immediate placement of the coated implants in the extraction sockets. This primary stability will ensure new bone growth to provide the more stable secondary stability. The biocompatibility of the coral graft and its role as an osteoconductor would have encourage this very useful phenomena in implantology.